Pattern Visual Evoked Potentials in Dyslexic versus Normal Children - Heravian, Javad (J Ophthalmic Vis Res, 2015)
PURPOSE: Presence of neurophysiological abnormalities in dyslexia has been a conflicting issue. This study was performed to evaluate the role of sensory visual deficits in the pathogenesis of dyslexia. METHODS: Pattern visual evoked potentials (PVEP) were recorded in 72 children including 36 children with dyslexia and 36 children without dyslexia (controls) who were matched for age, sex and intelligence. Two check sizes of 15 and 60 min of arc were used with temporal frequencies of 1.5 Hz for transient and 6 Hz for steady-state methods. RESULTS: Mean latency and amplitude values for 15 min arc and 60 min arc check sizes using steady state and transient methods showed no significant difference between the two study groups (P values: 0.139/0.481/0.356/0.062). Furthermore, no significant difference was observed between two methods of PVEPs in dyslexic and normal children using 60 min arc with high contrast (P values: 0.116, 0.402, 0.343 and 0.106). CONCLUSION: The sensitivity of PVEP has high validity to detect visual deficits in children with dyslexic problem. However, no significant difference was found between dyslexia and normal children using high contrast stimuli.